Analysis of the Application of Character Values in the History Subject of Specialization Class XI Madrasah Aliyah - Sukino, Pujo; Jannah, Miftahul (Global Education Journal, 2025)
This research aims to describe in a complete and comprehensive manner the application of character education in the history subject of specialization at MA Mathla'ul Anwar Pontianak. The research method used is descriptive with a qualitative approach. The research techniques used are direct communication, indirect communication and documentation. Research Tools, Observation Guides, Interview Guides, and Learning Documents. The results of the study include 1). The lesson plan for students of class XI IPS MA Mathla'ul Anwar Pontianak which is oriented towards instilling student character values has been made and well arranged in the syllabus. 2). History learning in grade XI students of Social Studies MA Mathla'ul Anwar Pontianak instills many character values that students can learn and follow. The character values instilled in students are 1). Religious, 2). Intrica, 3). Tolerance, 4). Discipline, 5). Creativity. 6). Independence, 7). Democracy, 8). Curiosity, 9). Love of the Homeland, 10). Communication, 11). Like to Read, 12). Social Care, 13). A sense of responsibility.  3). The factors that inhibit teachers in instilling student character values can be seen from: a) Each student is different so that the acceptance of instilling character values will be different. b). Different background factors of students.